(untitled) (Journal of Patan Academy of Health Sciences, 2024)
Introduction: Hospitalization of a child is a challenging and stressful experience for parents, often leading to heightened anxiety and reduced satisfaction with healthcare services. This study aims to identify the level of parental satisfaction with nurses’ communication and caring behaviours in the children’s ward. Method: A cross-sectional analytical study was conducted among 278 parents of children admitted in Children Ward of Patan Hospital. Parents were purposively selected and interviewed using self-structured questionnaire. Data analysis was done using SPSS version 20. Level of satisfaction was analyzed using frequency, percentage, mean and standard deviations. Association between levels of satisfaction with demographic variables were analyzed using chi-square test. Result: A total of 199(71.58%) parents were mothers. 209(75.18%) children had no prior hospitalizations. 116(41.73%) had a hospital stay of 4 to 7 days. Related to overall parental satisfaction, 203(73.02%) of the parents were satisfied, with mean of 3.32±0.54. Regarding communication, 173(62.20%) parents were satisfied, with mean of 3.22±0.53. Similarly, regarding caring behaviour, 212(76.30%) parents were satisfied, with mean of 3.51±0.62. Conclusion: The findings of the study showed that more than three fourth of the parents were satisfied with caring behaviour of nurses, whereas, one third parents were dissatisfied with communication by the nurses. The areas of least satisfaction were availability of nurses when needed, ward orientation provided on admission, information provided on ward routines and procedures. Therefore, these areas should be considered while providing care to the children admitted to children ward.